A sensitivity study of the WRF-Chem ozone forecast for Slovenia. (2015) - Žabkar, Rahela; Honzak, Luka
Extensive efforts have been devoted in recent years to develop an air quality forecasting system for Slovenia. In the present study, the results of an experimental real-time WRF-Chem forecast are evaluated for the summertime conditions, when ozone exceedances were measured during three heat wave events. The main focus of the paper is the assessment of model sensitivity to the domain setup and anthropogenic emission dataset used for Slovenia. To reduce model errors due to these two important sources of model uncertainties, significant efforts are needed either by increasing the computational power (domain setup and resolution) or by constructing an improved emission dataset based on detailed information about emissions, often deficiently available. In the study, the impact of these two sources of model uncertainties on ozone daily maximum predictions over a geographically complex area is explored.